A Metal‐Organic Framework with Nonpolar Pore Surfaces for the One‐Step Acquisition of C2H4 from a C2H4 and C2H6 Mixture. (31st August 2022) - Di, Zhengyi; Liu, Caiping; Pang, Jiandong; Zou, Shuixiang; Ji, Zhenyu; Hu, Falu; Chen, Cheng; Yuan, Daqiang; Hong, Maochun; Wu, Mingyan
Abstract: Because C2 H4 plays an essential role in the chemical industry, economical and energy‐efficient separation of ethylene (C2 H4 ) from ethane (C2 H6 ) is extremely important. With the exception of energy‐intensive cryogenic distillation, there are few one‐step methods to obtain polymer‐grade (≥99.95 % pure) C2 H4 from C2 H4 /C2 H6 mixtures. Here we report a highly stable metal‐organic‐framework (MOF) FJI‐H11‐Me(des) (FJI‐H=Hong's group in Fujian Institute of Research on the Structure of Matter) which features one‐dimensional hexagonal nonpolar pore surfaces constructed by aromatic rings and alkyl groups. This FJI‐H11‐Me(des) adsorbs C2 H6 rather than C2 H4 between 273 and 303 K. Practical breakthrough experiments with C2 H4 containing 1 % C2 H6 have shown that FJI‐H11‐Me(des) can realize the acquisition in one‐step of polymer‐grade, 99.95 % pure C2 H4 under various conditions including different gas flow rates, temperatures and relative humidity. Abstract : The metal‐organic framework FJI‐H11‐Me(des) which has nonpolar pore surfaces can directly give polymer‐grade C2 H4 from C2 H4 /C2 H6 mixtures at different gas flow rates, temperatures, and relative humidity. This separation is possible because it adsorbs C2 H6 rather than C2 H4 between 273 and 303 K.